Transnational environmental governance the emergence and effects of the certification of forests and fisheries - Gulbrandsen, Lars.; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar Pub., 2010)
In recent years a wide range of non-state certification programs have emerged to address environmental and social problems associated with the extraction of natural resources. This book provides a general analytical framework for assessing the emergence and effectiveness of voluntary certification programs. It focuses on certification in the forest and fisheries sectors, as initiatives in these sectors are among the most advanced cases of non-state standard setting and governance in the environmental realm.
1. Introduction -- 2. Non-state governance : an analytical framework -- 3. The emergence of forest certification -- 4. The adoption and impact of forest certification -- 5. Forest certification in Sweden and Norway -- 6. Spillover to the fisheries sector : the Marine Stewardship Council -- 7. The adoption and impact of fisheries certification -- 8. The spread and institutionalization of certification programs -- 9. Conclusions.
Includes bibliographical references (p. 183-203) and index.
Keywords: Environmental policy -- Internaional cooperation; Environmental management; Forests and forestry; Fisheries; Electronic books